Between Principles and Actions: ASEAN and Indonesia in Dealing With The Political Crisis In Myanmar - Gunawan, Tedi (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2024)
This article explains the role of ASEAN in addressing the political crisis and human rights violations in Myanmar, focusing on Indonesia's leadership as the ASEAN Chair in 2023. Following the 2021 military coup in Myanmar, which garnered global attention, ASEAN endeavored to formulate the Five Point Consensus through a constructive approach to tackle this crisis, yet its implementation remains constrained. This article uses a case study method to evaluate ASEAN's response to Myanmar's post-coup situation. The initial adoption of the